2017
DOI: 10.4103/neuroindia.ni_785_15
|View full text |Cite
|
Sign up to set email alerts
|

A study on the clinical outcomes and management of meningitis at a tertiary care centre

Abstract: Aseptic meningitis was found to be the predominant type among all different varieties of meningitis. An increased incidence of meningitis was seen in patients with diabetes mellitus. The incidence of seizures was high in viral/aseptic meningitis. The empirical treatment given in most of the cases was ceftriaxone. Isolation of the culpable organisms was possible in a very few cases due to the usage of empirical antibiotics prior to the performance of the lumbar puncture for the diagnostic analysis of the cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 2 publications
3
14
1
Order By: Relevance
“…As other previous studies have shown [17,46], the CSF parameters were diagnostic for bacterial meningitis and did not differ between the two groups; therefore, these parameters were still helpful for the diagnosis of meningitis.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…As other previous studies have shown [17,46], the CSF parameters were diagnostic for bacterial meningitis and did not differ between the two groups; therefore, these parameters were still helpful for the diagnosis of meningitis.…”
Section: Discussionsupporting
confidence: 63%
“…Diabetes mellitus is steadily increasing in western societies, and its association with the development of several types of infection is well-known [4,8,11,16,[19][20][21]. On the other hand, common infections in diabetic patients may be caused by unusual pathogens, and the presentation and course may be different from those without DM, which may delay the correct diagnosis and the adequate therapy [9][10][11][12][13][14][15][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar study conducted on a 5-year retrospective clinical data in East England during [17] showed that highest prevalence of fever and headache (82% each), and neck rigidity was one of it. The other study done in India also revealed the same finding [25].…”
Section: Fig 1 Organisms Isolated From Csf Cultures Of Patients Of supporting
confidence: 66%
“…Similarly, Yerramilli et al in 2017 studied 147 cases of suspected meningitis in a tertiary hospital in India and found the incidence of TBM to be around 28%. 11 Out of 100 suspected cases of meningitis, 22 were diagnosed as TBM in our study. Clinical findings on presentation were headache (87%), fever (78%), neck rigidity (69%), seizure (52%) and 74% had altered sensorium.…”
Section: Discussionmentioning
confidence: 79%